Profile of Metacognitive Awareness and Motivation of Biological Education Students of Riau Islamic University in Online Learning During the Covid-19 Pandemic - Yeyendra Yeyendra; Saiful Ridlo; Endang Susilaningsih; Budi Naini Mindyarto (International Conference on Science, Education, and Technology, 2022)
Abstrak. This study aims to determine the profile of metacognitive awareness and motivation of biology education students at the Islamic University of Riau. This type of research is survey research. The research population is all students of biology education at the Islamic University of Riau as a hypothetical population. The research sample amounted to 83 students. 27 students 2 semester, 15 students 4 semester and 41 students 6 semester. Data collection used a metacognitive awareness scale and an intrinsic motivation scale. The results showed that the metacognitive awareness of Biology Education Study Program students from the survey data showed that most or 49.39% of students were in the Still Very At Risk (MSB) category. There are no more students who fall into the category of underdeveloped metacognitive awareness (BBB). As many as 18.07% of Biology Education students have entered the category of starting to develop (MB). As many as 24.09% have well developed metacognitive abilities so that they are in the Well Developed (OK) category, and 8.43% are in the very well developed (super) category. Student motivation of Biology Education Study Program from survey data shows that a small percentage or 1.20% of student motivation is still in the very poor category. A total of 33.73% are still in the less category. Most or 39.76%. student motivation is still in the sufficient category. A total of 21.69% were in the good category and 3.62% had motivation in the very good category.